1993
DOI: 10.1007/bf01215923
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular features of esophageal cancer cells

Abstract: More than 70 cell lines were established from esophageal cancer, including 15 TE-series cell lines established by the authors. This article reviews molecular and cellular features of esophageal cancer cells from studies using these cell lines as well as primary tumors. The subjects reviewed include primary cultures of normal epithelium of the esophagus and of esophageal tumors, their growth and differentiation properties, chromosomal aberrations, protein kinase C, growth factors and their receptors, oncogenes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
171
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(177 citation statements)
references
References 45 publications
5
171
1
Order By: Relevance
“…Het1A cells were grown in BEGM medium (Biowhittaker Inc, Chesterbrook, PA, USA). The TE series (Nishihira et al, 1993) and KYSE series (Shimada et al, 1992) of esophageal cancer cells were grown in RPMI-1640 containing 10% fetal bovine serum. Retroviral and lentiviral production and transduction were previously described .…”
Section: Mutational Studiesmentioning
confidence: 99%
“…Het1A cells were grown in BEGM medium (Biowhittaker Inc, Chesterbrook, PA, USA). The TE series (Nishihira et al, 1993) and KYSE series (Shimada et al, 1992) of esophageal cancer cells were grown in RPMI-1640 containing 10% fetal bovine serum. Retroviral and lentiviral production and transduction were previously described .…”
Section: Mutational Studiesmentioning
confidence: 99%
“…The TTn cell line was established from a transplanted tumour in a nude mouse, the primary lesion being the same as that from which the TT cell line was established. It has been reported that all these cell lines were transplantable in nude mice (Takahashi et al, 1990;Galiana et al, 1993;Nishihira et al, 1993). TE-2, TE-8, and TE-13 have the wild type of p53 (Barnas et al, 1997;Itoshima et al, 2000;Akimoto et al, 2001).…”
Section: Cell Linesmentioning
confidence: 99%
“…The human oesophageal squamous cancer cell lines TE-2, TE-5, TE-9, and TE-13 were obtained from the Cell Resource Center for Biomedical Research Institute of Development, Aging and Cancer (Tohoku University, Sendai, Japan) (Nishihira et al, 1993). Cell lines KYSE170 and KYSE180 were kindly provided by Dr Shimada (Kyoto University, Kyoto, Japan) (Shimada et al, 1992).…”
Section: Cells and Cell Culturementioning
confidence: 99%